TINJAUAN TERHADAP LEMBAGA YUDIKATIF DALAM SISTEM HUKUM INDONESIA - dewi, erna (PRAEVIA, 2010)
The research studies about judicative body in Indonesia law system. This research uses jurisdiction normative approach. The result of research indicates that the role of judicative body as an independent body is free form government or political involvement, in the same rule as constitution of UUD NKRI 1945, meanwhile the inhibiting factors in reaching indevendence form jurisdiction body is not only from its law enforcement, law doer and also society in general who has not supported to create law country and law supreme yet.